2014
DOI: 10.1007/s13277-014-2013-y
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SPRY4-IT1 is upregulated in esophageal squamous cell carcinoma and associated with poor prognosis

Abstract: LncRNA SPRY4-IT1 has been shown to promote the progression of melanoma. However, the role of lncRNA SPRY4-IT1 in human esophageal squamous cell carcinoma (ESCC) remains unclear. The purpose of this study is to investigate the clinical significance and biological functions of SPRY4-IT1 in ESCC. The expression levels of lncRNA SPRY4-IT in 92 ESCC patients and 8 ESCC cell lines were evaluated by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). The prognostic significance was evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 27 publications
1
74
0
Order By: Relevance
“…The TUG1 lncRNA is emerging as a novel player in the disease state of bladder urothelial carcinoma and may have potential roles as a biomarker and a therapeutic target in bladder urothelial carcinoma [10]. The lncRNA SPRY4-IT1 is increased in esophageal squamous cell carcinoma tissues compared to that in the adjacent noncancerous tissues and is significantly associated with the clinical pathological stages and the overall survival rate of the disease [11]. Unfortunately, the emerging functional role of lncRNAs in ccRCC remains largely unknown.…”
Section: Proliferation Invasion Migrationmentioning
confidence: 99%
“…The TUG1 lncRNA is emerging as a novel player in the disease state of bladder urothelial carcinoma and may have potential roles as a biomarker and a therapeutic target in bladder urothelial carcinoma [10]. The lncRNA SPRY4-IT1 is increased in esophageal squamous cell carcinoma tissues compared to that in the adjacent noncancerous tissues and is significantly associated with the clinical pathological stages and the overall survival rate of the disease [11]. Unfortunately, the emerging functional role of lncRNAs in ccRCC remains largely unknown.…”
Section: Proliferation Invasion Migrationmentioning
confidence: 99%
“…Previously, multiple studies reported that in different types of cancer there was abnormal expression of lncRNA, indicating that the same lncRNA may serve different functions in different types of cancer. For instance, a lncRNA named SPRY4 intronic transcript 1 (SPRY4-IT1) was reported to be overexpressed in melanoma, renal cell carcinoma, esophageal squamous cell carcinoma, breast cancer, bladder cancer and glioma, and associated with poor prognosis and promotion of tumor growth (24)(25)(26)(27)(28)(29). Certain studies also demonstrated that SPRY4-IT1 expression was decreased in non-small-cell lung cancer and gastric cancer, and acted with significant antitumor function in these two types of cancer (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies show that the transcription and function of SPRY4-IT1 is independent from its host gene SPRY4 although they may be regulated by the same transcriptional machinery [9] . Studies show that SPRY4 expression levels were not significantly changed after SPRY4-IT1 knockdown, suggesting that SPRY4-IT1 directly rather than SPRY4 indirectly induced the phenotypic changes following the knockdown of SPRY4-IT1 [10] .…”
Section: Long Non-coding Rna Spry4-it1mentioning
confidence: 98%
“…Knockdown of SPRY4-IT1 blocked melanoma cell invasion and proliferation, and increases apoptosis, indicating that the abnormal upregulation of SPRY4-IT1 expression may have an important role in the molecular etiology of human melanoma [8] . Moreover, In esophageal squamous cell carcinoma (ESCC) patients, studies showed that SPRY4-IT1 levels were significantly higher not only in ESCC tissues and cells [10] , but also in patients plasm samples [11] , and the ESCC patients with higher SPRY4-IT1 expression had an advanced clinical stage and poor prognosis than those with lower SPRY4-IT1 expression. Moreover,studies also found that SPRY4-IT1 is up-regulated and associated with aggressive progression and poor prognosis in renal cancer [12] , gastric cancer [13] , breast cancer [14] and bladder cancer [15] , indicating that SPRY4-IT1 may become a novel potential prognostic biomarker for these malignant solid tumors.…”
Section: Spry4-it1 and Different Solid Tumorsmentioning
confidence: 99%